Looking Local: An Exploration of Texas Residents’ Perceptions of the GO TEXAN Certification Program to Develop Brand Positioning Strategies - Laura Morgan Fischer; Courtney Gibson; Kayla Powers (Journal of Applied Communications, 2023)
State agricultural certification programs allow consumers to knowingly purchase products grown or produced in their state. However, consumers may not be aware of or understand the concept behind these certification programs. This study examined Texas residents’ awareness and perceptions of one state agricultural certification program, GO TEXAN. To position a brand and develop key messages, communicators must be aware of how the audience views the brand, its key qualities and characteristics, and the information channels to distribute the messages. To do so, we distributed a survey instrument embedded in Qualtrics to a panel of Texas residents. We found respondents were generally unaware of the GO TEXAN certification program; however, the results of this study provide evidence of the consumers preferred products and qualities of GO TEXAN’s certified products. We suggest communicators use elements of brand positioning to develop strategic key messages that are relevant to target audiences. Specifically, messages should be developed with key frames highlighting product freshness, flavor, taste, and purchase convenience. Communication efforts should be developed to provide emphasis to these attributes on the product label, at farmers markets, and at places of purchase. Further, we recommend future research should explore how types of key messages impact brand awareness, loyalty, and willingness to purchase.
Keywords: Branding; Brand Positioning; Consumer Preferences; Product Attributes; State Certification Programs; Marketing